ChemInform Abstract: Flow Chemistry: Intelligent Processing of Gas‐Liquid Transformations Using a Tube‐in‐Tube Reactor. Issue 14 (April 2015) - Brzozowski, Martin; O'Brien, Matthew; Ley, Steven V.; Polyzos, Anastasios
Abstract: Review: 55 refs.